632 Know the score: evaluation of an intervention to reduce levels of drunkenness in a UK nightlife area. (1st September 2016) - Quigg, Zara; Ford, Kat; Butler, Nadia; Hardcastle, Katie; Hughes, Karen
Abstract : Background: In the UK the sale of alcohol to drunk people is illegal; however drunkenness remains common in nightlife environments. To address drunkenness in a UK nightlife area, an intervention was implemented to increase awareness of such legislation and to support bar staff compliance with the law. Methods: Pre- (n = 260) and post- (n = 318) intervention nightlife patron surveys were implemented exploring: drinking behaviours; expectations and tolerance of drunkenness; and knowledge of the law. The post-intervention survey additionally explored public awareness and perceptions of the intervention, and potential behavioural change as a result of the intervention. Results: The majority of pre-intervention survey participants had consumed alcohol; 63% of drinkers had preloaded. Drinkers expected units of alcohol consumed over the course of the night was 17.9 units. The majority expected their, and other people's, level of drunkenness to be high when leaving the city's nightlife. Over half believed that if someone was drunk and tried to get served alcohol in a bar in the city centre they would be served. Four in ten thought it was legal for a bar server to sell alcohol to someone who was already drunk. Post-intervention: significantly more participants knew that it is illegal for a bar server to sell alcohol to someone who is already drunk; significantly less agreed that getting drunk is socially acceptable; and significantly less reported preloading. Conclusions: The intervention presents an important step in working towards preventing the sale of alcohol to drunks and reducing associated harms. The evaluation suggests that the intervention may have increased knowledge of the laws around the service of alcohol to drunks amongst nightlife users, changed the perceived acceptability of drunkenness and decreased preloading. Despite this, post-intervention surveys illustrated that excessive alcohol consumption and drunkenness remain key features of the night-time economy.